Association of Mu-Opioid Receptor Expression With Long-Term Survival and Perineural Nerve Invasion in Patients Undergoing Surgery for Ovarian Cancer - Zhang, Hao; Qu, Mengdi; Sun, Caihong; Wang, Yanghanzhao; Li, Ting; Xu, Wei; Sun, Zhirong; Zhang, Xiaoguang; Guo, Kefang; Chen, Wankun; Sun, Minli; Miao, Changhong (Frontiers in Oncology, 2022)
Background: Ovarian cancer is one of the deadliest cancers worldwide. Increasing studies have shown that mu-opioid receptor (MOR) expression could negatively impact the long-term survival of cancer patients. This study aims to explore the impact of MOR expression on survival outcomes in ovarian cancers. Methods: The retrospective cohort study included women undergoing primary debulking surgery (PDS) for ovarian cancer from January 2015 to December 2018. MOR expression and OPRM1 gene expression were measured in tumor and normal tissue. Primary outcomes were overall survival (OS) and disease-free survival (DFS). Secondary outcomes included perineural invasion (PNI), intraoperative sufentanil consumption, length of stay (LOS), and verbal numerical rating scale (VNRS) on postoperative day1 (POD1), POD3 and POD5. Results: There were no significantly difference in OS rates in patients with high versus low levels of MOR (1-year OS: 82.9% versus 83.3%, P=0.632; 3-year: 57.8% versus 59.1%, P=0.473; 5-year: 22.4% versus 23.1%, P=0.226, respectively) in the ovarian cancers. There were no significant differences in DFS between the groups. Intraoperative sufentanil consumption, rates of PNI and VNRS on POD1 were higher in MOR high expression group compared with the MOR low expression group. Conclusion: MOR is not an independent predictor of worse survival in ovarian cancers but is associated with higher rates of perineural invasion.